Persistent currents, flux quantization and magnetomotive forces in normal metals and superconductors (Review Article) - Kulik, Igor O. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The notion of persistent current comes back to orbital currents in normal metals, semiconductors and even insulators displaying diamagnetic behavior in weak magnetic fields, but came to focus at the discovery of current persistence and magnetic flux quantization at large fields in atomically big but macroscopically small (mesoscopic) objects. The phenomenon bears much similarity with supercurrents in superconductive metals. We will review progress in developing of our understanding of the physical and technological aspects of this phenomenon. The exact solution for currents, magnetic moments and magnetomotive forces (torques) in crossed magnetic fields are presented. Time-dependent phenomena in crossed magnetic and electric fields, and in possibility of spontaneous persistent currents and of work extraction from static and dynamic quantum states are discussed.